AN EXISTENTIAL-ISLAMIC DIALOGUE: REINTERPRETING SPIRITUALITY TO OVERCOME MODERN "UNHOMELINESS" - Anam, Rifqi Khairul; Alamsyah Halim (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
Addressing the modern spiritual crisis of ’unhomeliness’—rooted in Heidegger’s ’forgetting of Being’ (Seinsvergessenheit) and inadequately met by conventional responses—this article constructs an ’existential-Islamic dialogue’. Drawing from Heideggerian thought and Ali Syari’ati’s reinterpreted spirituality, this framework synthesizes meditative practices (Denken, Gelassenheit) with the cultivation of an authentic, justice-oriented community (ummah). The central finding is that this synthesis offers a viable path to integrate profound individual transformation with concrete social and political engagement. The article concludes by addressing key challenges, such as essentialism and utopianism, while using the Indonesian context as a key point of reference.